Nebenbestimmungen bei der Zulassung von Abfallentsorgungsanlagen unter besonderer Berücksichtigung des Instruments der Sicherheitsleistung - Rumann, Welf-Tilo (Universitätsverlag Göttingen, 2020)
The subject of the work is the ancillary provisions for the licensing of waste management facilities, which on the one hand restrict the requested permission, but on the other hand often make it possible to issue it in the first place. The main focus of the work is a detailed examination of the security aspects, which play a special role in the structure of collateral clauses. It will be examined to what extent the regulations on security in the licensing of waste management facilities in the BImSchG and KrWG allow an appropriate balance of conflicting interests in the tension between economy and environmental protection. In this context, the history, the scope for action in the official order of the security aspects and the constitutional implications are also examined in more detail. In addition, the specifics of waste management facilities are shown which justify the fact that the regulations of security for the other types of facilities of the BImSchG are generally not applicable.